Dampak Peternakan Ayam Terhadap Sanitasi Lingkungan Di Desa Leahari Kecamatan Leitimur Selatan Kota Ambon Provinsi Maluku - Celsy Maitimu; Daniel Anthoni Sihasale; Roberth Berthy Riry (Jurnal Pendidikan Geografi Unpatti, 2025)
This study aims to explore the impact of poultry farming on environmental sanitation in Leahari Village, Leitimur Selatan District, Ambon City. The research uses a descriptive analysis method with a qualitative approach, where data is collected through observation, interviews, and documentation study. The findings show that poultry farming in Leahari Village provides positive impacts on the local economy, such as creating job opportunities and supporting micro, small, and medium enterprises (MSMEs). However, poultry farming also leads to negative impacts such as air, water, and soil pollution due to improper waste management. Ammonia gas from chicken manure causes air pollution, while liquid waste contaminates groundwater and soil. To address this, the study suggests the implementation of biogas technology for waste management, educating the community about waste management, and strengthening regulations and government supervision. This research provides recommendations for improving the management of poultry farming waste to be more environmentally friendly and sustainable.